2013
DOI: 10.1074/jbc.m113.453837
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Allophanate Hydrolase

Abstract: Background: Allophanate hydrolase (AH) is essential for urea utilization in many organisms. Results: We determined the crystal structure of the Kluyveromyces lactis AH and performed mechanistic studies. Conclusion: Our work revealed that the AH N and C domains catalyze sequential reactions and provided insights into their catalysis. Significance: The catalytic mechanism of the C domain might expand the knowledge of decarboxylation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…The role of the smaller C-terminal domain is less clear, however. Fan et al (37) suggested that the C-terminal domain of AH Kl is catalytic, decarboxylating N-carboxycarbamate to form carbamate and carbon dioxide. On the basis of in silico substrate docking and mutagenesis studies, it was proposed that a histidine residue in the C-terminal domain (His492; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of the smaller C-terminal domain is less clear, however. Fan et al (37) suggested that the C-terminal domain of AH Kl is catalytic, decarboxylating N-carboxycarbamate to form carbamate and carbon dioxide. On the basis of in silico substrate docking and mutagenesis studies, it was proposed that a histidine residue in the C-terminal domain (His492; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a report from Fan et al, the authors proposed that the C-terminal domain of AH Kl is involved in the hydrolysis of N-carboxycarbamate, the unstable product of AH-mediated allophanate deamination ( Fig. 1) (37). Moreover, in silico substrate docking suggested that a C-terminal histidine residue (His492) plays an important catalytic role (37).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Protein thermodynamic stability, a classic and essential characteristic of the prevalent biopolymer, is frequently investigated in fundamental research, [1][2][3][4][5][6][7][8][9][10][11] drug discovery, [12][13][14][15][16] and protein engineering. [17][18][19][20] Evaluation on protein unfolding/folding energy is one of primary methods to understand protein conformational stability, 21 protein mutation effects, 22 and property changes of small compounds binding to protein.…”
Section: Introductionmentioning
confidence: 99%